Environmental and socio-demographic individual, family and neighborhood factors associated with children intestinal parasitoses at Iguazú, in the subtropical northern border of Argentina - Rivero, Maria Romina; De Angelo, Carlos; Nuñez, Pablo; Salas, Martín; Motta, Carlos E.; Chiaretta, Alicia; Salomón, Oscar D.; Liang, Song (PLOS Neglected Tropical Diseases, 2017)
Author summary Enteroparasites are among the main issues in public health arena, especially in children of vulnerable communities from developing countries. We performed a combined analysis of the factors that describe parasite prevalence in children and their environment. Our result evidenced a combined effect of socio-demographic and environmental factors acting at different scales (individual, family, and neighborhood) to determine the parasitic infections patterns and health risk of children at Iguazú Municipality in Argentina. Therefore, this work shed light on the multiple and multilevel factors involved in parasitic diseases, emphasizing the need for action in socio-health and environmental structural issues, not only from the decision-making authorities but also from the individuals, families and communities in favor of promoting healthy environments and healthy individuals.